Worrying times: the fear of crime and nostalgia. Issue 3 (3rd July 2021) - Farrall, Stephen; Gray, Emily; Jones, Phil Mike
ABSTRACT: As well as finding empirical relationships between victimisation, key socio-demographic variables and various psychological and environmental processes, criminologists have long suspected that the feelings now identified, corralled together and labelled as 'the fear of crime' have roots in the wider shifts in the social and economic bases of society. In this paper, and using survey data from a nationally representative sample of Britons aged over 16 ( n  = 5781), we explore the relationships between feelings of political and social nostalgia and the fear of crime. We find that nostalgia is strongly related to crime fears, and, indeed, stronger even than variables such as victimisation, gender and age (three of the frequently cited associates of fear). We go on to explore these relationships further in terms of different socio-economic classes and relate feelings of nostalgia and fear to their recent (ie, post-1945) historical trajectories.